Responding to price changes in the context of growing international competition - Bondos, І. (Видавництво Львівської політехніки, 2013)
In terms of increasing the number of companies operating on the market, both domestic and foreign companies, right approach to respond to the different types of competitor’ price moves becomes extremely important. The purpose of this article is to present the proper approach to respond to price competition. Adequate reaction to competitor's price reduction may prevent price war, which is absolutely a negative phenomenon. В умовах збільшення кількості компаній, що функціонують як на вітчизняному, так і на закордонному ринках, надзвичайно важливим стає правильний підхід до відповіді на різні типи змін конкурентної ціни. Подано правильний підхід щодо відповіді на цінову конкуренцію. Адекватна реакція на зниження конкурентної ціни може запобігти ціновій війні, яка є абсолютно негативним феноменом.
Відповідь на зміни цін у контексті зростаючої міжнародної конкуренції
Keywords: pricing; price competition; price war; price response; ціноутворення; цінова конкуренція; цінова війна; відповідь на ціну